2020
DOI: 10.3390/v12050553
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Dromedary Camel HEV in Domestic and Imported Camels from Saudi Arabia

Abstract: Hepatitis E Virus (HEV) imposes a major health concern in areas with very poor sanitation in Africa and Asia. The pathogen is transmitted mainly through ingesting contaminated water or food, coming into contact with affected people, and blood transfusions. Very few reports including old reports are available on the prevalence of HEV in Saudi Arabia in humans and no reports exist on HEV prevalence in camels. Dromedary camel trade and farming are increasing in Saudi Arabia with importation occurring unidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Saudi Arabia is the world’s largest importer of DCs from African countries, while countries of the horn of Africa are the main exporter of camels to the Arabian Peninsula 2 , 24 . In Saudi Arabia, we recently showed that the prevalence of DcHEV antibodies in domestic camels is slightly higher than in camels imported from Africa 25 . Identifying DcHEV genotypes and performing detailed molecular and phylogenetic characterization of the virus in DCs is critical for surveillance, understanding the evolution of human infections and designing appropriate control and preventive measures.…”
Section: Introductionmentioning
confidence: 90%
“…Saudi Arabia is the world’s largest importer of DCs from African countries, while countries of the horn of Africa are the main exporter of camels to the Arabian Peninsula 2 , 24 . In Saudi Arabia, we recently showed that the prevalence of DcHEV antibodies in domestic camels is slightly higher than in camels imported from Africa 25 . Identifying DcHEV genotypes and performing detailed molecular and phylogenetic characterization of the virus in DCs is critical for surveillance, understanding the evolution of human infections and designing appropriate control and preventive measures.…”
Section: Introductionmentioning
confidence: 90%
“…This chronicity is likely to have been opportunistic and influenced by immunosuppressive medication to prevent organ rejection. In a separate paper, HEV was demonstrated to be seroprevalent in 23.1% of dromedary camels which originated in Sudan and Saudi Arabia (El-Kafrawy et al 2020 ). Due to the recent discovery of this genotype of HEV, and its implication in human infection, further research is warranted to investigate how widespread camel HEV is within countries which regularly consume camel products to determine the risk such products may have for the foodborne transmission of HEV.…”
Section: Hev In Other Land Animals and Animal Productsmentioning
confidence: 99%
“…Alternatively, this higher prevalence might indicate a possible risk factor for the infection in domestic camels responsible for this higher prevalence. In a recent study on the same subset of samples [21], we showed that the seroprevalence of DcHEV in domestic camels is slightly higher than those of imported camels (25.4% vs. 22.4%, p value = 0.3). Observations from both studies warrant the need for further investigations to identify the possible risk factor that is causing this higher prevalence.…”
Section: Discussionmentioning
confidence: 63%
“…Sequences from domestic camels formed a separate cluster with reported sequences from Kenya, Somalia, and UAE (except for three samples) while imported sequences clustered with one isolate from UAE indicating a possible common source of infection. Previous studies have demonstrated the HEV seropositive DCs in Africa and the Middle East [17,21,[30][31][32][33]. A recent study [33] showed a higher seroprevalence in dromedaries in Israel where they found a seroprevalence of 68.6%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation